(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
In this article, the author describes in detail the organization of accounting in construction enterprises, the main purpose of cost management accounting in the accounting system. Also, taking into account the importance of the problem of cost management within the construction enterprise, a cost management system in accounting is proposed, and in order to reasonably reduce costs, the essence of the effective cost management system in construction enterprises is shown.